Appropriation d’un savoir délibératif en formation à l’enseignement à partir d’une approche d’analyse de récits en groupe - Serge Desgagné; Hélène Larouche; Matthias Pepin; Marie-Josée Dumoulin; Geneviève Audet (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article focuses on training in deliberation amongst future pre-school and primary-level teachers based on group analysis of experienced teachers’ narratives. Is deliberation relevant for pre-service teacher training? Can we establish the relevance from the point of view of research, whilst highlighting what future teachers learn from the process? In order to address this issue, we present results analysing deliberation sequences, based on experienced teachers’ narratives that have been used as “case studies”. The interactionist analysis leads to three ways of building up deliberation capacities. Knowledge on deliberation is discussed in terms of a collective meaning regarding a zone of “responsibility”, a zone of “control”, and a zone of “virtue”. This insight on future teachers deliberation process is captured by Schön’s reflective practitioner model (Schön, 1983).